Design and compatibility analysis of a solar panel integrated UHF antenna for nanosatellite space mission - Rahmatillah, Rahmi (2018)
A compact UHF antenna has been presented in this paper for nanosatellite space mission. A square ground plane with slotted rectangular radiating element have been used. Coaxial probe feeding is used to excite. The rectangular slot of the radiating patch is responsible for resonating at lower UHF bands. One of the square faces of the nanosatellite structure works as the ground plane for the slotted radiating element. The fabricated prototype of the proposed antenna has achieved an impedance bandwidth (S11< -10dB) of 7.0 MHz (398 MHz– 405 MHz) with small size of 97 mm× 90 mm radiating element. The overall ground plane size is 100 mm × 100 mm × 0.5 mm. The proposed antenna has achieved a gain of 1.18 dB with total efficiency of 62.5%. The proposed antenna addresses two design challenges of nanosatellite antenna, (a) assurance of the placement of solar panel beneath the radiating element; (b) providing about 50% open space for solar irradiance to pass onto the solar panel, enabling the solar panel to achieve up to 93.95% of power under of normal conditions.